Understanding the Role of HDL during COVID-19 Infection - Garg, Iti; Srivastava, Swati; Kumar, Bhuvnesh (Coronaviruses, 2021)
Background: Recently emerged COVID-19 pandemic has caused a large number of deaths with lacs of confirmed cases worldwide posturing a grim situation and severe threat to public health. There is an imperative necessity of analyzing emerging clinical and laboratory data of COVID-19 patients, which may contribute to elucidate the pathogenic mechanism and development of effective prevention and treatment countermeasures. Methods: Under this article, the emerging role of High-Density Lipoprotein (HDL) was analyzed by collecting recently published articles related to this field having clinical data of COVID-19 patients. Results: Based on the recently published reports of laboratory-confirmed COVID-19 infected hospitalized patients it was consistently observed that levels of HDL were low at the time of admission to hospital and remained relatively low during the disease course i.e., treatment, recovery, and discharge stage. It was also reported critically that levels of HDL in the patients, those did not survive, decreased continuously until death. Conclusion: These clinical reports of patients have risen the concern about probable infection and worsen the clinical outcome of a healthy person having a compromised level of HDL for COVID-19 infection. Eventually, these findings stated that there is a strong association of low HDL levels with a higher risk of COVID-19 infection and further severity of the illness. Proper attention is needed to understand the significance of altered quantity and quality of HDL in COVID-19 patients compared to healthy controls, so that appropriate therapies could be given at the right time to combat severity and mortality due to this infection.
Keywords: Cholesterol